Regulation of Drug Procurement and Supply Chain Management in Indonesian Hospitals: Implications for Drug Availability and Mitigation of Drug Shortage - Arrasily, Nailul Fithri; Minarsih, Tri Jenny; Hartono, Budi; Daud, Alfani Ghutsa (Jurnal Ilmiah Ekotrans & Erudisi, 2025)
Pharmaceutical management in hospitals is a critical component of the healthcare system, directly influencing service quality and operational sustainability. This study examines the relationship between the pharmaceutical regulatory framework established by the Ministry of Health (Kemenkes) and the National Agency of Drug and Food Control (BPOM) and the operational performance of pharmaceutical Supply Chain Management (SCM) in Indonesian hospitals. A Systematic Literature Review (SLR) using a Scoping Review approach was conducted to synthesize quantitative evidence on drug procurement regulations, distribution, and inventory efficiency. Secondary data show that 34.7% of hospitals experience shortages of essential medicines at least once a year, and 80% of pharmaceutical distributors (PBFs) fail to meet the maximum three-day delivery lead time. This highlights a substantial gap between comprehensive regulations, such as Ministry of Health Regulation No. 17 of 2024 on Telepharmacy and BPOM Regulation No. 20 of 2025 on Good Distribution Practice (CDOB), and operational logistics implementation. The main challenge lies not in regulatory design but in weak enforcement of logistical discipline and supplier monitoring. Recommended strategies include performance-based contracts linking lead-time compliance to penalties or incentives and continuous data-driven training for pharmaceutical personnel. Strengthening the synergy between regulatory frameworks and operational discipline is essential to ensure sustainable drug availability and high-quality healthcare services in Indonesia.